Srategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di SDN 5 Pulasan Kabupaten Sijunjung - Roni Indra Partini; Asmendri Asmendri (Departement of Mathematics Education, 2023)
This study describes the principal's strategy, the obstacles that occur, and the efforts made by the principal in improving teacher performance at SDN 5 Pulasan, Sijunjung Regency. Data collection was carried out using interview and observation techniques. Data analysis was carried out by analyzing the results of the research based on data reduction, data presentation, and drawing conclusions. The results showed that: The principal's strategy in an effort to improve teacher performance at SDN 5 Pulasan, Sijunjung Regency. The obstacles that occur are that some teachers do not have the ability to utilize learning technology, lack of facilities and infrastructure and teacher discipline is still low. Efforts made by the school principal in improving teacher performance at SDN 5 Pulasan, Sijunjung Regency, namely fostering teachers intensely and continuously in teacher performance development activities, besides that, the principal motivates and makes stricter disciplinary regulations at school.